THE UNCONSCIOUS IN HEGEL’S PHILOSOPHY AND HEGEL’S ANTICIPATION OF PSYCHOANALYSIS - Tereshchenko, Y. D. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The article deals with revision of problem of the unconscious in the system of Hegel’s philosophy. The author tries to demonstrate an inconsistency of popular ideas about Hegelian theories that regard «Hegel» only as a preacher of a «reasonable» and «necessary» structure of reality and consciousness. The author of the article sets himself the task of drawing the attention of contemporary Hegelian scholarship to the fact that he had worked a lot on the processes taking place in the «unconscious mind», which became the object of close attention to psychoanalytic theories.